PELATIHAN CONTENT WRITING ESSENTIALS BAGI SISWA SMA BUDI AGUNG: MENINGKATKAN LITERASI DIGITAL GENERASI MUDA - Felix, Antonius; Kembau, Agung Stefanus; J. Makarawung, Reynard; Bernanda, Devi Yurisca; Haryadi, Alessandra; Budiarjo, Ken (Jurnal Pengabdian dan Kewirausahaan, 2026)
Indonesia faces a gap in digital content production literacy among the younger generation, yet most lack the basic skills to produce high-quality, impactful digital content. This gap has the potential to limit the role of the younger generation in the digital economy ecosystem, leaving them more dominant as consumers than creative actors. This community service program (PKM) aimed to bridge this gap through interactive content writing training for Budi Agung High School students. The implementation employed a participatory approach combining material presentation, Q&A sessions, and digital-based educational games using the Blooket platform. Conducted on December 9, 2025, the activity involved 19 students. Evaluation through feedback questionnaires with four assessment components Educational, Objective, Accountable, and Transparent showed average ratings above 3.5 on a 4-point scale, with the highest score of 3.63 on Educational, Objective, and Accountable aspects. These findings indicate that the training was well received by participants and perceived as beneficial in enhancing their understanding of content writing, as well as increasing their awareness of opportunities in the digital creative economy. This activity is expected to be one of the efforts of the Bunda Mulia University Digital Business Study Program in supporting the development of content writing at the secondary education level.